A novel ionic liquids phase change absorption system for carbon dioxide capture and utilization - Yuqing Chang; Yujiao Wu; Ruoke Liu; Yuan Jiang; Zhijun Zhou; Tianlin Wang; Xiaochun Chen (Fuel, 2024)

Research on Bearing Characteristics of Gravity Anchor in Clay - Jianxing Yu; Pengfei Liu; Yang Yu; Xin Liu; Haoda Li; Ruoke Sun; Xuyang Zong (Journal of Marine Science and Engineering, 2023)
The applications and studies of gravity anchors in the ocean are becoming more and more extensive. Most of the research, however, has been directed toward the bearing properties of sand. Relatively less attention has been paid to the bearing properties of gravity anchors in clay. Clay is widely distributed on the seabed. The research on the bearing capacity of gravity anchors in clay is of great significance for offshore oil exploitation. Therefore, the gravity anchor was investigated by conducting reduced-scale model tests, and the bearing process of gravity anchors in clay was simulated through a 3D finite element method. Model tests and numerical simulations were used to determine the capacity curve and the V-H failure envelope of gravity anchors in clay. The simulation results and the test results are in good agreement. The failure form of the gravity anchor in clay was revealed by 3D finite element analysis. The effect of cohesion, internal friction angle, and mooring point height on bearing capacity have been studied. The influence of the height of the mooring point on the V-H failure envelope curve was explored by changing the height of the mooring point. The formula of the V-H failure envelope curve suitable for different mooring point heights was obtained.

Study on Fatigue Spectrum Analysis and Reliability Analysis of Multilayer Flexible Riser - Jianxing Yu; Fucheng Wang; Yang Yu; Haoda Li; Xin Liu; Ruoke Sun (Journal of Marine Science and Engineering, 2022)
Multilayer composite flexible risers have been widely used in engineering. However, this type of structure is complex, as there are influences between layers. Moreover, a range of uncertain factors need to be considered in fatigue analysis. Therefore, it is difficult to perform the fatigue analysis research of multilayer flexible risers. In this paper, the fatigue spectrum analysis and reliability analysis method of a nine-layer flexible riser structure are proposed, and a complete fatigue and reliability analysis process for multilayer structures is developed. The theoretical basis of the fatigue spectrum analysis method is introduced, and the calculation program is described. Finite element software is used to analyze the stress of the multilayer flexible riser under the influence of the upper platform structure movement and the ocean current. Moreover, the stress response of the riser structure of each layer is obtained. According to this, the irregular wave load is simulated by the method of random number simulation, and the stress response spectrum is formed. Then, the appropriate S-N curve is selected to calculate the fatigue damage degree of each layer, and the fatigue damage nephogram is displayed, so as to analyze the structural fatigue damage. Finally, the uncertainty in the process of fatigue damage calculation is analyzed. According to the results, the methods of multilayer riser analysis are summarized and the future research directions are put forward.